2019
DOI: 10.1002/jcb.29240
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase 3 (GPX3) suppresses the growth of melanoma cells through reactive oxygen species (ROS)‐dependent stabilization of hypoxia‐inducible factor 1‐α and 2‐α

Abstract: In this study, we aimed to explore the mechanism of glutathione peroxidase 3 (GPX3) in the growth of malignant melanoma (MM) cells by hypoxia‐inducible factor‐1α (HIF1‐α) and HIF2‐α regulating the metabolism through reactive oxygen species (ROS). The messenger RNA and protein expression of GPX3, HIF1‐α, HIF2‐α in tissues, and cell lines were measured by reverse transcription‐quantitative PCR and Western blot analysis. A375 cells were transfected with GPX3 overexpression plasmid, small interfering RNA (siRNA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Nonetheless, antioxidant enzymes, including the GPx family members, are important regulators of these signaling cascades by manipulating levels of oxidants at cellular redox signaling hubs [28,85]. We highlight several studies in Section 3.2 where GPx3 has been implicated in modulating the activity of redox signaling pathways in cancer cells [32,[86][87][88][89][90].…”
Section: Disease Association With Aberrant Gpx3mentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, antioxidant enzymes, including the GPx family members, are important regulators of these signaling cascades by manipulating levels of oxidants at cellular redox signaling hubs [28,85]. We highlight several studies in Section 3.2 where GPx3 has been implicated in modulating the activity of redox signaling pathways in cancer cells [32,[86][87][88][89][90].…”
Section: Disease Association With Aberrant Gpx3mentioning
confidence: 99%
“…Gene hypermethylation Poor patient outcome, potential biomarker [125] Inhibit activation of Erk-NF-κB-cyclin B1 pathway [86] Melanoma Gene hypermethylation Cancer progression, poor patient outcome [111] Inhibit expression of hypoxia-inducible factors 1α and 2α [89] [116] Myeloid leukemia N/D Cancer progression, poor patient outcome [116,129] Ovarian cancer N/D Cancer cell survival under anchorage independence and oxidative stress [14] Ovarian clear cell adenocarcinoma N/D Chemoresistance [130] As summarized in Table 1, several studies have reported a decrease or loss of GPx3 expression in tumor tissues [61][62][63]86,87,[109][110][111][112][113][114][115]. In many of these cancers, downregulation of GPx3 parallels cancer progression, and is often associated with poor patient outcome [62,90,109,110,123].…”
Section: Altered Gpx3 Expression and Role In Tumor Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that GPX-1 is crucially involved in the development and progression of colorectal cancer (8), thyroid cancer (9), and kidney cancer (10); meanwhile GPX-2 has been found to regulate invasion, metastasis, apoptosis, and prognosis in cancers including pancreatic cancer (11), bladder cancer (12), cervical cancer (13), and nasopharyngeal carcinoma (14), suggesting that GPX2 may be an oncogene. Furthermore, GPX-3 methylation has been linked to multiple cancers, has potential value in predicting prognosis (15)(16)(17), and is also considered to be a tumor suppressor (18)(19)(20)(21). GPX-4 regulates ferroptotic cancer cell death, and is related to the therapy resistance of cancer cells (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased levels of GPX3 are related to increased proliferation, motility, invasiveness, and poor prognosis [88]. Overexpression of GPX3 decreased the viability of melanoma cells and inhibited their growth in a xenografts model [89]. This data points to the important role of GPX3 inhibiting melanoma progression, and this subject should be more addressed in the field.…”
Section: Glutathione Systemmentioning
confidence: 95%